(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Irritable bowel Syndrome (IBS) is a functional disorder of abdominal pain or discomfort associated with altered bowel habit. Microscopic colitis is a chronic inflammatory condition associated with non bloody diarrhoea and characteristic histological finding. The subset of diarrhoea predominant IBS is having similarity in presentation with microscopic colitis. Objective: To assess the prevalence and characteristics of microscopic colitis in Diarrhoea predominant Irritable Bowel Syndrome (IBS-D). Materials and Methods: This observational study was conducted at the department of Gastroenterology, Combined Military Hospital, Dhaka during the period of January 2011 to June 2011. Initially 100 cases of diarrhoea predominant IBS who met Rome III criteria were included. Among those 100 cases, 57 were male and 43 were female. Mean age was 46 years ±2.8 SD(range 18-72). Six patients were subsequently excluded because of some macroscopic abnormalities at colonoscopy. Finally 94 patients of clinical IBS-D whose colonoscopy were normal, biopsy specimens were taken from caecum, transverse colon, descending colon, sigmoid and rectum. Microscopic colitis was diagnosed on the basis of evidence of increased intraepithelial lymphocytes of ≥20/100 inter cryptal epithelial cells and infiltration of lamina propria by mixed inflammatory cells. Overlap of other symptoms between Microscopic Colitis (MC) and IBS-D were also evaluated. Results: Among the 94 patients of clinical IBS-D, 23(24%) patients were histologically proved to have microscopic colitis. Besides Rome III criteria, there was significant overlap of other symptoms. Occasional fever and infrequent arthralgia 7% and 26% vs 4% respectively) but tenesmus, passage of excessive mucus and heart- burn were more prevalent in IBS-D than MC (35% vs 13%, 32% vs 4% and 32 vs 9% respectively). Among the 23 cases of MC, 13(57%) patients were female and 10(43%) patients were male. Mean age of microscopic colitis was 56 years ±2.6 SD (range 25-72). Regarding subtypes of microscopic colitis, 21(91%) patients had lymphocytic colitis (LC) and 2 (9%) patients had collagenous colitis (CC). Of the lymphocytic colitis 11 were female and 10 were male and of the 02 cases of collagenous colitis all were female. MC affected mostly the transverse colonie 11(48%) cases and the next common site was caecum ie 8(35%) cases. Conclusion: A good percentage of diarrhoea predominant IBS are actually having microscopic colitis. MC is more common in female and elderly persons. In all elderly patients of IBS-D full colonoscopy should be done and biopsy should be taken from multiple sites to exclude microscopic colitis. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 57-62